Supernatural World as Alternative Escapism Reflected in Neil Gaiman’s Coraline - Amalia Andrane Sakya Galih; Thohiriyah (Universitas Islam Negeri Palopo, 2025)
The background study for the research lays the foundation by contextualizing the importance of exploring the relationship between the supernatural realm and escapism in Neil Gaiman's novel ‘Coraline’(2002). Neil Gaiman's